Adherence of Clostridium difficile spores to Caco-2 cells in culture - Daniel Paredes‐Sabja; Mahfuzur R. Sarker (2012)
Clostridium difficile is the causative agent of the majority of antibiotic associated diarrhoea cases. C. difficile spores are recognized as the persistent and infectious morphotype as well as the vehicle of transmission of CDI. However, there is a lack of knowledge on how C. difficile spores interact with the host's epithelial surfaces. In this context, we have characterized the ability of C. difficile spores to adhere to human Caco-2 cells. Despite the similarities in spore-surface hydrophobicity between spores of C. difficile and Clostridium perfringens (another enteric pathogen that also sporulates in the gut), spores of C. difficile adhere better to Caco-2 cells. Adherence to Caco-2 cells was significantly reduced when C. difficile spores were treated with trypsin. Sonication of C. difficile spores altered the ultrastructure of the outermost exosporium-like structure, releasing two protein species of ~40 kDa and significantly reduced spore hydrophobicity and adherence to Caco-2 cells. Using a trifunctional cross-linker, we were able to co-immunoprecipitate four protein species from the surface of Caco-2 cells. In conclusion, this study provides evidence that C. difficile spores adhere to human intestinal enterocyte-like cells through spore- and enterocytic-surface-specific ligand(s) and/or receptor(s).